Peran Material Pengemas Primer dan Sekunder dalam Menjaga Mutu Obat - Ghina Faiha; Hana Salma Cantika; Nor Latifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Packaging plays an important role in maintaining the quality, stability, and effectiveness of medicines, both in the form of pharmaceutical preparations and herbal products. This review article aims to analyze the role of primary and secondary packaging materials through literature studies from various relevant journals. The method used was a literature review of four selected national and international journals that discussed the influence of packaging on product stability, information effectiveness, and product image in the eyes of consumers. The results of the study show that primary packaging functions to protect products directly from environmental influences, while secondary packaging functions in distribution, storage, and strengthening visual and branding aspects. Innovations such as the use of adsorbent plastics and visual redesign have been proven to increase stability and consumer confidence in the product. It can be concluded that packaging is a crucial aspect that not only maintains the physical-chemical quality of the product, but also shapes consumer perception and compliance.